Peningkatan Keterampilan Komunikasi dan Tanggung Jawab Lingkungan melalui Pelatihan MC dan Lomba Recycle - Ardiansyah, Bagas Raka; Salman, Salwa Nabila; Dewi, Amanda Kusuma; Cahyarani, Elvina; Novita, Vivi Tria; Rahim, Abdur; Riduansyah, Muhammad Iqbal; Arimbi, Vina; Rafi Aji, Prihandoko Rizqi; Hasdifa, Abu Rizal; Sutoyo, Sutoyo (Universitas Muhammadiyah Yogyakarta, 2025)
Community Service (PKM) in Padukuhan Kangkung B, Ngeposari Village, Semanu Subdistrict, Gunungkidul Regency, aims to empower the community through communication skills training and waste management initiatives. Several underlying community issues in Padukuhan Kangkung B highlight the need for this PKM program. These issues include a lack of effective communication skills among residents, which hinders social interaction and collaboration within the community. Additionally, inadequate waste management has led to environmental problems such as pollution and waste accumulation, negatively affecting public health. The objective of this program is to provide mentoring and training in communication skills for children and teenagers, as well as guidance on innovative and creative waste management strategies to motivate community members. The method employed in this program involves stages of socialization, mentoring, and evaluation. The target groups are children and teenagers for the communication skills program, and mothers from each neighborhood unit (RT) for the waste management innovation activities. Program success is evaluated through competitions. The outcomes of the program include Master of Ceremony (MC) training for children, which successfully increased their self-confidence and public speaking abilities, and a recycling competition that fostered creativity and raised community awareness of the importance of recycling. The activities were carried out over one month, from January 30 to February 28, 2025, using various methods including observation, socialization, and hands-on practice. The evaluation results show a positive impact on participants, as evidenced by 11 children joining the MC training and 8 of them successfully applying public speaking skills, along with 6 creative recycled products. Despite challenges in time management and group coordination, this initiative is expected to lay the foundation for future development and encourage active community participation in environmental preservation and quality of life improvement